2015
DOI: 10.1039/c5fo00671f
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin induces autophagic cell death in human papillary thyroid carcinoma BCPAP cells

Abstract: Apigenin, abundantly present in fruits and vegetables, is recognized as a flavonoid with anti-inflammatory, antioxidant and anticancer properties. In this study, we first investigated the anti-neoplastic effects of apigenin on papillary thyroid carcinoma (PTC) cell line BCPAP cells. Our results show that apigenin inhibited the viability of BCPAP cells in a dose-dependent manner. A large body of evidence demonstrates that autophagy contributes to cell death in certain contexts. In the present study, autophagy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 39 publications
2
61
1
Order By: Relevance
“…The cells treated with 50 μmol/L apigenin showed a high rate of autophagic vacuole formation, and the cells treated with 100 μmol/L showed a high rate of cells in apoptosis 89. A recent study reported that apigenin could induce autophagic cell death in human thyroid cancer BCPAP cells, as evidenced by Beclin-1 accumulation, conversion of LC3 protein, p62 degradation, and significantly increased AVO formation 90. These results suggest that apigenin simultaneously induced apoptosis and autophagy.…”
Section: Role Of Apigenin In Autophagymentioning
confidence: 71%
See 1 more Smart Citation
“…The cells treated with 50 μmol/L apigenin showed a high rate of autophagic vacuole formation, and the cells treated with 100 μmol/L showed a high rate of cells in apoptosis 89. A recent study reported that apigenin could induce autophagic cell death in human thyroid cancer BCPAP cells, as evidenced by Beclin-1 accumulation, conversion of LC3 protein, p62 degradation, and significantly increased AVO formation 90. These results suggest that apigenin simultaneously induced apoptosis and autophagy.…”
Section: Role Of Apigenin In Autophagymentioning
confidence: 71%
“…The role of autophagy in cancer cells is dichotomous, with some reports demonstrating autophagy helps cells to survive under stress, and other reports indicating that autophagy ends in apoptosis in the absence of cell recovery. Zhang et al90 found that apigenin could induce both apoptosis and autophagy, while inhibition of autophagy with the small molecule inhibitor 3-MA reduced cell death, indicating that apigenin was associated with autophagic cell death in BCPAP cells. Ruela-de-Sousa and et al86 investigated the molecular mode of action of apigenin and found that apigenin-induced autophagy was not followed by apoptosis in TF1 leukemia cells.…”
Section: Role Of Apigenin In Autophagymentioning
confidence: 99%
“…[22] reported that apigenin directly bound DNA in prostate epithelial cell lines, although the mechanisms by which this binding may induce DNA damage must be further explored. Apigenin-induced G2/M phase accumulation and apoptosis have been frequently reported [4, 5, 2325]. However, delayed cell cycle progression at G1/S phase is also observed in several kinds of malignant tumors [2628].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, along with Akt inhibitors, apigenin can further enhance the efficacy of radioiodine therapy for thyroid cancer patients [195]. Apigenin-induced cell death has been shown to involve autophagy in papillary thyroid cancer, perhaps because of ROS stimulation, induction of DNA damage and G2/M phase cell cycle arrest [196]. Targeted radioiodine therapy, used in thyroid cancer, depends on thyrotropin-mediated selective stimulation of Na+/I− Symporter (NIS)-mediated radioactive iodide uptake (RAIU) by thyroid cells.…”
Section: 0 Effect Of Apigenin In Various Human Cancersmentioning
confidence: 99%